Nanodosimetry and Its Role in Bridging Medical, Biological, and Applied Physics in Cancer Therapy - Alawei, Nabaa Kareem Wadi; musaa, Athraa Muajjal Ubaid; Abadi, Abbas Abdullah Razaq; Za’iri, Kawthar Hussein Abdullah; Ali, Muntazir Akram Arhim (American Journal of Botany and Bioengineering, 2025)
Nanodosimetry emerges as an interdisciplinary link connecting medical, biological, and applied physics with cancer therapy. The presence of nanotechnology in all these fields, alongside clinical progress witnessed in several cancer centers, underlines its integrative capacity. The adoption of innovative radiation fields and ion beams, exemplified in advanced centers and associated applications, provides impetus for new forms of radiation protection and modulating technologies for cancer radiosensitivity. The fundamental role of nanodosimetry lies in elucidating molecular mechanisms underpinning radiation interactions at the cellular level. As a result, foundational knowledge and experimental data serve as a basis for developmental tools, enveloped by modeling and simulation of radiation interactions at the organ scale.